THE APPRECIATION FOR THE POETS AND LITERARY WORKS OF ARABIC POETRY IN THE EARLY ISLAMIC ERA - Fachiroh, Wirdah (International Journal of Social Service and Research, 2024)
This article aims to provide an answer to the accusations of those who accuse that Islam absolutely prohibits the chanting of literary works, especially Arabic poems, based on a misunderstanding of the Qur'anic verses 224-227 of Surah Assyu'aro, in addition to explaining how the development of Arabic poems in the early era of Islam and the attention given by the Prophet Muhammad (PBUH) to Arab poets in the Islamic Era. The research contributes by clarifying misconceptions about the prohibition of poetry in Islam. The study provides a nuanced understanding of the role and acceptance of poems in early Islamic culture. This would include studying how their preferences and criticisms, particularly those related to poets like Zuhair bin Abi Sulma, influenced the literary landscape and aligned with the broader goals of Islamic governance and da'wah.